Dermoscopic evaluation of efficacy of 308 nm Excimer Laser in treatment of alopecia areata: A prospective study - Kalegowda, Deepadarshan; B Madegowda, Shashikumar; Rajegowda, Harish M; Rathod , Meghana P (Journal of Pakistan Association of Dermatologists, 2024)
Objective To evaluate the therapeutic response of Excimer Laser in treatment of alopecia areata by dermoscopy. Methods A total 34 patches in 24 patients were administered with 308nm excimer laser twice a week for 12 weeks and followed up after 3 months of last sitting. Treatment response was evaluated using regrowth scale (RGS) and dermoscope was used to assess disease activity, response to treatment and side effects. Results Among 34 patches, 4 patches (13%) showed excellent response, 16 patches (47%) showed good response, 7 patches (20%) showed moderate response and 7 patches (20%) showed poor response. Dermoscopically, 27 patches (responders) showed reduction in black dots, yellow dots, broken hairs, tapering hairs and appearance of short vellus hairs which are signs of remitting disease, compared to 7 patches (nonresponders), who showed no change. Yellow dot was the most common dermoscopic finding seen among 85.3% at baseline. Conclusion The excimer laser is one among the efficacious treatment for Alopecia areata. Dermoscopy is useful to assess the response to treatment and side effects.